In Situ Regulation of Macrophage Polarization to Enhance Osseointegration Under Diabetic Conditions Using Injectable Silk/Sitagliptin Gel Scaffolds. Issue 3 (16th December 2020) - Xiang, Geng; Liu, Keyin; Wang, Tianji; Hu, Xiaofan; Wang, Jing; Gao, Zhiheng; Lei, Wei; Feng, Yafei; Tao, Tiger H.
Abstract: As a chronic inflammatory disease, diabetes mellitus creates a proinflammatory microenvironment around implants, resulting in a high rate of implant loosening or failure in osteological therapies. In this study, macroporous silk gel scaffolds are injected at the bone–implant interface for in situ release of sitagliptin that can regulate macrophage response to create a prohealing microenvironment in diabetes mellitus disease. Notably, it is discovered that sitagliptin induces macrophage polarization to the M2 phenotype and alleviates the impaired behaviors of osteoblasts on titanium (Ti) implants under diabetic conditions in a dose‐dependent manner. The silk gel scaffolds loaded with sitagliptin elicite a stronger recruitment of M2 macrophages to the sites of Ti implants and a significant promotion of osteointegration, as compared to oral sitagliptin administration. The results suggest that injectable silk/sitagliptin gel scaffolds can be utilized to modulate the immune responses at the bone–implant interface, thus enhancing bone regeneration required for successful implantation of orthopedic and dental devices in diabetic patients. Abstract : A silk gel scaffold loaded with sitagliptin is developed to in situ regulate macrophage polarization from M1 to M2 phenotypes and improve osteointegration of endosseous implants at the bone–implant interface under diabetes conditions. The study provides a new insight into the mechanisms underlying diabetes‐induced implant failure and represents an innovative strategy to promote osteointegration in diabetic patients with hyperglycaemia.